Distopía y apocalipsis en la poesía de Óscar Hahn y Gonzalo Millán - Galindo V., Óscar (Anales de Literatura Hispanoamericana, 2004)
The article analyses dystopian and apocalyptic elements in two contemporary Chilean poets, Óscar Hahn and Gonzalo Millán, as part of a reflection on the alienation and degradation that characterizes urban life. However, from the deepest structures of these poets' texts, it detects a tension between the dystopian-apocalyptic discourse and the utopian discourse which creates diverse allegorical and literary meanings.